Prolonged QTc interval in adults with diabetic ketoacidosis: is it only electrolyte disturbance? - Osama A Khalil; Ghada M Samir; Ayman M.E.M Sadek (SpringerOpen, 2019)
Context Cardiac arrhythmia in diabetic ketoacidosis (DKA) is a well-known complication that is usually a result of electrolyte imbalance. Another frequently missed cause of arrhythmia is the QT interval prolongation, which is not always attributed to electrolytes disturbance. Aim We aimed to explore the frequency of QTc interval prolongation among patients with DKA in the medical ICU, the association with serum electrolytes and pH, and the implication on the outcome. Patients and methods We carried out a cross-sectional cohort study on patients with DKA admitted to medical ICU. We had worked on 72 patients with DKA by performing the routine investigation including ECG follow-up during the hospital stay. Maximum QT interval in all measured leads (QTmax) and heart rate-corrected QTmax (QTmaxc) were calculated in milliseconds according to Bazett's formula. We used SPSS, version 20.0, with the following statistical tests: Shapiro-Walk, Student's t, Pearson's correlation, logistic regression, receiver operating characteristic curve analysis, and relative risk. Results The frequency of QTmaxc interval prolongation without electrolyte imbalance was seen in 46 (63.9%) patients. pH revealed to be the most significant independent risk factor for QTmaxc interval prolongation (odds ratio=8.39, 95% confidence interval: 1.67-18.06) with a cutoff value less than 7.03, with sensitivity of 56% and specificity of 44%. QTmaxc prolongation carried a relative risk of ∼1.7-fold for mortality in patients with DKA. Conclusion Acidosis carries an independent risk for QTmaxc interval prolongation in the absence of electrolytes abnormalities, with related poor ICU outcome in patients with DKA.